(untitled) (Fiep Bulletin - online, 2013)
To study the schoolchildren of the different ethnic group health became a frequent practice among the researchers, because they are factors essences to establish parameters of references on the physical fitness of this population. In the present study, it looked for to describe the behavior of the physical fitness variables related to the athletic acting for all of the children ages from seven to 12 practicing years of age of sports in the Municipal Centers of Sport and Leisure of Manaus (AM) Brazil being 588 male and 362 female totaling 950 participants. The variables of the physical fitness were the test of seat-and-reach, modified situp and the run/walk in the time of nine minutes. The analysis of the data extracted of the medium values of the physical fitness variables revealed differences significant estatisticament, with high levels of the boys motor acting and coming girls of the studies accomplished by other researchers in relation to the to the boys and girls of the present study. This information can be justified so much for the proposition of the routine of evaluation of the attributes of appraised motor acting, as for the influence of the practice level to regulate of physical exercise, influencing in the representativeness of the results of the tests of flexibility, force/resistance and resistance cardio respiratory.